(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article addresses the issue of the parastatal violence lived in Argentina between 1973 and 1976 within the framework of the so-called “fight against subversion”. We comparatively analyze the regional characteristics of the parastatal violence in two cases: the city of Bahia Blanca and the area “Gran Mendoza”. We intend to think about forms of interregional movement of repressive practices between parastatal groups and axes of regional similarities/differences with the prospect of revealing organizational schemes of the parastatal violence.